Sistem Pengontrolan Dan Keamanan Rumah Pintar (Smart Home) Berbasis Android - Dodon Yendri; Rahmi Eka Putri (JITCE (Journal of Information Technology and Computer Engineering), 2018)
The tightness of one's activities sometimes makes people forget about security and comfort issues such as forgetting to lock the door, forgetting to turn off the lights or other electronic equipment so that it makes the house unsafe and also have an impact on energy waste. This research objective was to design a home security control system using Raspberry Pi connected to several electronic equipment, wifi, and internet communication networks. Remote control and monitoring using a smartphone. The test was carried out on ACS712 current sensor, PIR (Passive Infra Red) sensor, DHT22 temperature and humidity sensor, two lights and one webcam and buzzer. The test results show that the system that is designed can display information on current values, temperature, and humidity and also can control the condition of the house by turning on and off two lights with a 100% success rate. The PIR sensor can detect the movement of people at a maximum distance of 5.5 meters and the webcam manages to capture objects when motion is detected, the notification will automatically be sent to the owner's smartphone and the buzzer will be activated immediately.